2022
DOI: 10.1101/2022.04.22.489199
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Aperiodic brain activity and response to anesthesia vary in disorders of consciousness

Abstract: In the human electroencephalogram (EEG), oscillatory power peaks co-exist with non-oscillatory, aperiodic activity. Although EEG analysis has traditionally focused exclusively on oscillatory power, recent investigations have shown that the aperiodic EEG component can distinguish conscious wakefulness from sleep and anesthetic-induced unconsciousness (Lendner et al. 2020). This study investigates the aperiodic EEG component of individuals in a disorder of consciousness (DOC), and how it changes in response to e… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 53 publications
3
12
0
Order By: Relevance
“…However, the spectral exponent significantly correlated with non-anoxic patients' CRS-R score (r(82)=0.33, p<0.05) (analysis 2). In line with previous research (Maschke, Duclos, Owen, et al 2022), a flatter exponent indicated a higher level of consciousness (see Figure 4 and 5). The correlation between the spectral exponent and non-anoxic patients' level of consciousness as well as its ability to distinguish responsive from unresponsive patients lost significance after p-value correction (see Figure 3 and 5).…”
Section: The Eeg Spectral Exponent Has More Diagnostic Value Than The...supporting
confidence: 92%
See 3 more Smart Citations
“…However, the spectral exponent significantly correlated with non-anoxic patients' CRS-R score (r(82)=0.33, p<0.05) (analysis 2). In line with previous research (Maschke, Duclos, Owen, et al 2022), a flatter exponent indicated a higher level of consciousness (see Figure 4 and 5). The correlation between the spectral exponent and non-anoxic patients' level of consciousness as well as its ability to distinguish responsive from unresponsive patients lost significance after p-value correction (see Figure 3 and 5).…”
Section: The Eeg Spectral Exponent Has More Diagnostic Value Than The...supporting
confidence: 92%
“…Even though the EEG spectral exponent has been historically neglected, mounting evidence attributes changes in the spectral exponent as an index of altered states of consciousness (Colombo et al 2019;Lendner et al 2020;Colombo et al 2023). In addition, our group previously demonstrated that patients in a DOC are often characterized by a total absence of oscillatory peaks (Maschke, Duclos, Owen, et al 2022). In the current study, we validate the previously shown diagnostic value of the aperiodic component for non-anoxic patients (Maschke, Duclos, Owen, et al 2022;Colombo et al 2023).…”
Section: The Eeg Spectral Exponent Has Diagnostic Value For Non-anoxi...mentioning
confidence: 93%
See 2 more Smart Citations
“…Recovery of consciousness is believed to co-occur with the emergence of a spectral peak in the lower frequency range (around 7 Hz), with a shift towards higher frequencies (first around 10 Hz and potentially around 20 Hz) during further recovery Edlow, Claassen, et al 2021. The relevance of EEG measurements in DoC is underscored by the notion that the re-emergence of physiological EEG features is associated with behavioral recovery Colombo et al 2023;Jørgensen and Holm 1998;Maschke et al 2023;Thibaut, Panda, et al 2021 and glucose uptake Annen et al 2023. Several hypotheses may explain the recovery of the EEG power spectrum in patients with DoC. One of these hypotheses, the meso-circuit hypothesis, states that the return of spectral peaks in the EEG power spectrum is a result of the restoration of excitation in the thalamocortical circuit and, more specifically, a more widespread cortico-striato-pallido-thalamic network N. D. Schiff 2010.…”
Section: Introductionmentioning
confidence: 99%